Determination of A1 and A2 β-casein in cow milk by high-performance liquid chromatography tandem mass spectrometry - Fengen Wang; Min Ding; Ruiju Li; Kun Wang; Xiuxin Zhao; Xia Li; Zengmei Li; Shiming Guo; Ligang Deng; Jianbin Li (Journal of Dairy Science)
ABSTRACT: A2 β-CN milk has gained widespread acceptance due to its nutritional benefits. To verify the authenticity and detect adulteration and contamination in A2 milk, we developed an HPLC-MS/MS method for determining the characteristic peptides of A1 and A2 β-CN in cow milk. The method demonstrated good specificity, sensitivity, and linearity for both A1 and A2 characteristic peptides, with limit of detection of 0.01 and 0.03 mg/L, limit of quantitation of 0.03 and 0.1 mg/L, and determination coefficients of 0.9994 and 0.9992, respectively. Whereas accuracy and precision were reasonable, the recoveries varied (69.4%–151%) across concentration levels (0.04, 0.2, and 1.0 g/kg), with higher recoveries for both peptides at low concentrations and lower recoveries for A2 peptide at medium and high concentrations, influenced by factors such as adsorption and ionization efficiency. We optimized the tryptic hydrolysis conditions, selecting a trypsin-to-casein ratio of 1:25 and a hydrolysis time of 6 h at 37°C. However, the hydrolysis of A1 and A2 β-CN was incomplete and asynchronous, exhibiting parabolic relationships with their respective concentrations, with hydrolysis degrees of 12.3% for A1 β-CN and 9.6% for A2 β-CN in pure powders. We finally established a regression model to calculate the actual proportion of A1 and A2 β-CN, with the detection limits of 5% for both β-CN. In the quantitation range of this model, A1 β-CN accounting for 10% to 80% or A2 β-CN accounting for 20% to 90%, the measured value of A1/A2 or A2/A1 was a power function relationship with the theoretical value. This method effectively verifies the authenticity of A1 and A2 milk, providing a reliable tool for detecting adulteration and contamination.